A WiMAX Network Architecture Based on Multi-Hop Relays - Voudouris, Konstantinos; Tsiakas, Panagiotis; Athanasopoulos, Nikos; Georgas, Iraklis; Zotos, Nikolaos; Stergiopoulos, Charalampos (IntechOpen, 2012)
None